The contribution of environmental factors to fish assemblages in the Río Acahuapa, a small drainage in Central America - Álvarez,Francisco S. (2017)
ABSTRACT The ichthyofauna of the Río Acahuapa was analyzed sampling 17 sites that included the basin main channel and its tributaries. Fish were collected using dip-nets, seine-nets and electrofishing. Fish standard length and species abundance were recorded. Species origin and salinity tolerance criteria were used to classify fish species. Water physicochemical variables, habitat structure and sampling sites elevation were recorded. A total of 33 fish species were registered, 12.1% are primary, 45.5% are secondary and 42.4% are of marine derivation. Fish species richness declined with increase of elevation (R2=0.55, p=0.0006). Two assemblages of fishes were identified: the first one associated to sites of low elevations (19-184 masl), composed mainly of secondary and marine-estuarine fish species related with high temperature, water velocity, river width, dissolved oxygen and low sand and silt substrate cover; the second one associated to sites of middle and higher elevations (185-519 masl), composed by primary and secondary freshwater fishes related with high pH, logs and rocks substrate cover. In summary, elevation and environmental variables contributed to the composition and distribution of fish in the Río Acahuapa.